1990
DOI: 10.1126/science.247.4938.59
|View full text |Cite
|
Sign up to set email alerts
|

A Light Source Smaller Than the Optical Wavelength

Abstract: A method has been developed for the efficient emission of light from subwavelength dimensions. It is based on packaging photons as molecular excitons, effectively reducing the volume of the light beam by 10(9) and making possible propagation through dimensions of 1 nanometer. Molecular microcrystals are grown in the tips of micropipettes that have inner diameters of 100 nanometers or less. Measurements are presented that demonstrate this improvement in transmission for pipettes of various diameters. The ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(68 citation statements)
references
References 15 publications
0
68
0
Order By: Relevance
“…Over the last decade, numerous experimental configurations have been proposed for studying single molecule photophysical phenomena triggered by nanometer size light fields [1][2][3][4][5][6][7][8]. These configurations involve the interaction of microscopic entities with their macroscopic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, numerous experimental configurations have been proposed for studying single molecule photophysical phenomena triggered by nanometer size light fields [1][2][3][4][5][6][7][8]. These configurations involve the interaction of microscopic entities with their macroscopic environment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most fruitful optical spectroscopic technique in small domains is scanning near-field optical microscopy (SNOM), which provides a spatial resolution better than the diffraction limit (λ/2) for imaging and spectroscopy applications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Molecular aggregates and microcrystals have been *The results of this paper were initially presented at The Jabłoński Centennial Conference on Luminescence and Photοphysics, July 23-27, 1998, Toruń, Poland. (835) the subject of SNOM study because of their heterogeneous properties on the solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A reproducible and efficient fabrication of the probe, therefore, becomes very important for PSTM. Some fabrication methods (Lieberman et al 1990, Pagnia et al 1990, Pohl et al 1984 have been reported, but sufficiently high reproducibility and detection efficiency have not yet been achieved and the tip diameter of the fabricated probe has not been small enough for resolving the nanometric scale structure of the sample. To solve these problems, a selective etching method using a buffered hydrofluoric (HF) acid as an etching solution has been applied to a single-mode fiber, fabricated by the vapor-phase axial deposition (VAD) method for fabricating the fiber probes (Jiang et al 1991;Pangaribuan et al 1992Pangaribuan et al , 1993.…”
Section: Introductionmentioning
confidence: 99%